All we are is dust in the wind: The social causes of a “subculture of coping” in the late medieval coversand belt - De Keyzer, Maïka (Journal for the History of Environment and Society, 2016)
Abstract Natural hazards posed major challenges to almost every pre-modern society. Even in the moderate climate zone of Europe, natural hazards such as floods, storm surges and sand drifts threatened entire societies and could decimate occupation and land exploitation in a region. Some societies, however, were able to prevent hazards from turning into disasters, while others repeatedly suffered from nature-induced catastrophes. The question therefore remains, how were some societies able to cope and create subcultures of coping, while others were not? By combining archaeological data, OSL studies and archival material I will advance that we have to alter the current paradigm that the Campine area was predominantly struck by disastrous sand drifts from the later Middle Ages onwards. We should focus on specific combinations of the distribution of power between smallholders and elites and the level of short-termism of the social interest groups to explain why the late medieval Campine area was able to design a subculture of coping to mitigate the effects of insidious sand drifts.